EKSTRAKSI EUGENOL DARI MINYAK DAUN CENGKEH DENGAN PELARUT NaOH DAN n-HEKSAN - Arifan, Fahmi; Yulianto, Mohamad Endy (Universitas Diponegoro, 2006)
Abstract Â Clove oil represent other side result from clove plantation. Clove leaf oil used permanent upon which to make isolateband derivative in many industry. In this research analyse concentration influence and ratio of solvent â€“ bait to yielded product rendemen. In a proses insulation of eugenol used process high rise liquid extraction. As a raw material is leaf clove oil, NaOH and n-heksan used as a solvent. In extraction with NaOH will be yielded Na eugenolat, so that have be eliminated the content of Natrium by using HCl 2 N. Later then its result be reextracted by using n-hexan. So that obtained pure eugenol and with randemen which is more. Ever greater of used solvent volume and concentration, hence eugenol which is extract will progressively mount. Â Key Word : eugenol, extraction